2016
DOI: 10.1101/cshperspect.a027847
|View full text |Cite
|
Sign up to set email alerts
|

Directional Fluid Transport across Organ–Blood Barriers: Physiology and Cell Biology

Abstract: Directional fluid flow is an essential process for embryo development as well as for organ and organism homeostasis. Here, we review the diverse structure of various organ-blood barriers, the driving forces, transporters and polarity mechanisms that regulate fluid transport across them, focusing on kidney-, eye- and brain-blood barriers. We end by discussing how cross-talk between barrier epithelial and endothelial cells, perivascular cells and basement membrane signaling contribute to generate and maintain or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 238 publications
(273 reference statements)
0
30
0
Order By: Relevance
“…The RPE tight junctions regulate the paracellular movement of solutes via size and charge selectivity ( Benedicto et al, 2017 ; Caceres et al, 2017 ; Naylor et al, 2019 ).Occludin and claudins determine the permeability and semi-selectivity of the TJs, and as such play critical roles in the oBRB ( Balda et al, 2000 ; Fields et al, 2019 ; Furuse et al, 1998 ; Günzel & Yu, 2013 ; Rosenthal et al, 2017 ). JAMs regulate TJ assembly and function by recruiting other proteins to the TJ and play an important role in the barrier property of TJs ( Balda & Matter, 2016 ; Orlova et al, 2006 ; Shin, Fogg & Margolis, 2006 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…The RPE tight junctions regulate the paracellular movement of solutes via size and charge selectivity ( Benedicto et al, 2017 ; Caceres et al, 2017 ; Naylor et al, 2019 ).Occludin and claudins determine the permeability and semi-selectivity of the TJs, and as such play critical roles in the oBRB ( Balda et al, 2000 ; Fields et al, 2019 ; Furuse et al, 1998 ; Günzel & Yu, 2013 ; Rosenthal et al, 2017 ). JAMs regulate TJ assembly and function by recruiting other proteins to the TJ and play an important role in the barrier property of TJs ( Balda & Matter, 2016 ; Orlova et al, 2006 ; Shin, Fogg & Margolis, 2006 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…[1][2][3][4] The blood-tissue barriers, for example, play a vital role in regulating drug transport from the capillaries to the targeted organs. 5 To exert functional activity, these capillaries typically consist of an endothelial cell layer and a basement membrane. More detailed, architectural, and organizational characteristics depend on organ-specific features giving rise to blood-tissue barriers variation from organ to organ.…”
Section: Introductionmentioning
confidence: 99%
“…In the formation of the oBRB, the fully mature RPE tight junctions (TJs) are formed, which have the role of limiting the paracellular movement of ions and water through the RPE monolayer and maintain the apical-basal distribution of the RPE transporters [57]. These features are crucial for maintaining retinal homeostasis since they allow for the formation of gradients that lead to directional fluid transport from the neural retina to the choroid [58]. Recent studies have shown that choroid endothelial cells (ECs) act as blood conduits, forming instructive niches for the differentiation, regeneration, and function of parenchymal cells, and may thus intervene in the regulation of ECs [59].…”
Section: Biological Signalling Process Of Retinamentioning
confidence: 99%